A combined pulse modulation-processing method for ADCP applications. (October 2015) - Han, Ning; Fang, Shiliang
Abstract: Acoustic Doppler Current Profiler (ADCP) based on the Doppler principle is the sonar for velocity measurements, which is mainly applied in the large-scale measurements of the oceanic current velocity. In order to satisfy the increasing requirement of high measurement resolution and accuracy compared with the traditional ADCP, this paper investigates the ambiguous functions of different signals and indicates that the pulse combined by several sinusoidal signals will improve the time resolution when keeping good frequency resolution. Then the present research proposes the modulation of a combined pulse as the ADCP׳s emitted signal, as well as the corresponding signal processing method. Two examples are demonstrated to show the effectiveness of the combined pulse modulation-processing method, and it is seen that: 1. the combined pulse has the same spatial resolution as one subpulse, while achieves better frequency resolution and better signal–noise ratio than the latter; 2. although the combined pulse results in a little worse signal–noise ratio than the long sinusoidal signal, the former has much higher spatial resolution; 3. the measurement accuracy of the combined pulse is better than the broadband coded-pulse when they have the same pulse width. Highlights: We indicate that the combined pulse improves the time resolution. We design the combined pulse as the emitted signal of ADCP. We propose the processing method corresponding to the emitted combined pulse. The proposed modulation-processing method has higher resolution and accuracy.